2009
DOI: 10.1007/978-3-642-04425-0_3
|View full text |Cite
|
Sign up to set email alerts
|

Representation and Traversal of Large Clabject Models

Abstract: Abstract. Multi-level modeling using so-called clabjects has been proposed as an alternative to UML for modeling domains that feature more than one classification level. In real-world applications, however, this modeling formalism has not yet become popular, because it is a challenge to efficiently represent large models, and providing fast access to all information spread across the metalevels at the same time. In this paper we present the model representation concept that relies on a permanent condensed view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Modeling exercises by domain experts and experiments with the transformation engine also showed that the new metamodeling framework was suitable. We also demonstrated that our memoryefficient representation method and the corresponding traversal algorithms scale to large models [19].…”
Section: Figure 4 Engine Model With Clabjectsmentioning
confidence: 97%
“…Modeling exercises by domain experts and experiments with the transformation engine also showed that the new metamodeling framework was suitable. We also demonstrated that our memoryefficient representation method and the corresponding traversal algorithms scale to large models [19].…”
Section: Figure 4 Engine Model With Clabjectsmentioning
confidence: 97%
“…The authors conclude that the complexity of extended and extensible models is dramatically reduced by applying multiple levels over the previously used flat modeling formalism. In [50] multi-level modeling was applied to industrial automation systems which consist of hundreds of model-elements. Their evaluation showed that multi-level modeling is applicable for real world scenarios containing big models.…”
Section: Related Workmentioning
confidence: 99%
“…In other multi-level frameworks, like [2], the main concern is the efficient navigation between meta-levels, but they do not consider the concrete syntax of model management languages. Nivel [3] is a multi-level metamodelling framework based on the weighted constraint rule language (WCRL).…”
Section: Approaches To Multi-level Meta-modellingmentioning
confidence: 99%